Syndromes Associated with Sexually Transmitted Infections in Lilongwe, Malawi: Burden and Trends, 2006 to 2015. Issue 6 (14th June 2021) - Matoga, Mitch; Chen, Jane S.; Kudowa, Evaristar; Kamanga, Gift; Mapanje, Clement; Massa, Cecilia; Ndalama, Beatrice; Bonongwe, Naomi; Nyirenda, Naomi; Mathiya, Esther; Jere, Edward; Ngoma, Edith; et al.
Abstract : Among sexually transmitted infection clinic patients in Lilongwe, genital discharge, lower abdominal pain, and ulcer syndromes were common. Trends in most sexually transmitted infection syndromes remained stable between 2006 and 2015. Supplemental digital content is available in the text. Abstract: Monitoring the burden of and trends in sexually transmitted infection syndromes is useful in informing syndromic management guidelines. Among sexually transmitted infection clinic patients in Lilongwe, Malawi, between 2006 and 2015, genital discharge, lower abdominal pain, and genital ulcer syndromes were common. Prevalence of most syndromes remained stable during the 10-year period.